Clinical patterns of psoriatic arthritis & association with age & gender among patients presenting to a tertiary care hospital - Sultan, Nadia; Chaudhry, Asad Ali; Butt, Ghazala; Rehman, Saima; Aman, Shahbaz; Shoaib, Tabinda (Journal of Pakistan Association of Dermatologists, 2020)
Background Psoriasis is a common skin condition, which is known to affect about 1-2% of the world population. PsA is a known extra-cutaneous complication of psoriasis, which has variably been reported to affect 5-40%.1 Objective To determine the clinical patterns of psoriatic arthritis & association with age & gender among patients of patients presenting to a tertiary care setting. Materials and Methods A cross sectional study conducted at OPD, Unit-I, KEMU Mayo Hospital, Lahore, conducted for six months from 20th August, 2013 to 20th February, 2014. Total sixty five patients of psoriatic arthritis diagnosed according to Moll & Wright criteria were enrolled & evaluated for the pattern of arthritis & its association with age & gender. Data entry and analysis was done by using SPSS 16. Results Among 65 cases of PsA, 44 (67.69%) M & 21 (32.31%) F, mean age 42.92±13.70 y, asymmetrical oligo-arthritis was most common pattern in 22 (33.85%). Most PsA cases were in their 2nd to 5th decade. Conclusion Most common pattern was asymmetric oligo-arthritis. Males of late young and middle age were affected the most.